Near-Disasters and a Looming Catastrophe: Reimagining the Year 1985 in Two Russian Blockbusters - Boele, Otto (Wiener Slawistischer Almanach, 2024)
The essay examines two Russian bigbudget films (Salyut-7 and The Icebreaker) from the aspect of “speculative history”. It argues that while both films fit in with a more general trend in Russian cinema to revive the collective memory of Soviet successes in sports and space exploration, they are unique in focusing on the waning years of the Soviet Union (rather than the “long 1970s”) and using dramatic irony to trigger feelings of nostalgia and resentment. By telling the stories of two spectacular rescue operations from 1985 and alluding to the nation’s impending loss of super power status, the films present us with a paradox: why did the Soviet Union collapse if it was still capable of executing such “impossible” missions? With this question we are invited to speculate that the “greatest geo-political catastrophe of the twentieth century” (Vladimir Putin) has always been somewhat suspicious and might have been avoided.